1987
DOI: 10.1203/00006450-198707000-00102
|View full text |Cite
|
Sign up to set email alerts
|

81. Upper Gi Tract Involvement in Children With Crohn's Disease

Abstract: 's Ilosp, London. studies wcre undertaken to assess the value of including base in ORS in (i) an animal model of intestinal secretion and (ii) children with acutc gastroenteritis. After exposure to cholera toxin, rat small intestine was perfused in situ with ORS containing base or identical OR5 in which base was replaced by chloride.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 0 publications
3
50
1
Order By: Relevance
“…Crohn's disease Gastritis and mucosal ulceration is found in 25±40% of children and adults with Crohn's disease, and upper gastrointestinal symptoms are commonly reported in these patients [34]. However, these symptoms often lead children to the evaluation for peptic ulcer disease and the treatment thereof, rather than a work-up for Crohn's disease.…”
Section: Other Disorders Of Acid``hypersecretion''mentioning
confidence: 98%
“…Crohn's disease Gastritis and mucosal ulceration is found in 25±40% of children and adults with Crohn's disease, and upper gastrointestinal symptoms are commonly reported in these patients [34]. However, these symptoms often lead children to the evaluation for peptic ulcer disease and the treatment thereof, rather than a work-up for Crohn's disease.…”
Section: Other Disorders Of Acid``hypersecretion''mentioning
confidence: 98%
“…It reveals that 38% of children of all ages have small bowel disease, 38% have small bowel and large bowel disease and 20% have large bowel disease. Other studies have shown that upper GI disease occurs in 30% to 40% of children [29]. Even higher rates (up to 71%) are seen in endoscopic studies [30,31] and perianal disease is found in 11% to 18% [32,33].…”
Section: Paediatric CD Disease Coursementioning
confidence: 95%
“…With the more uniform employment of EGD in pediatric CD patients, the prevalence of UGI involvement in pediatric CD has been better characterized. The pediatric literature suggests that the incidence of macroscopic UGI tract involvement in patients with CD can be as high as 30 % [ 11 ]. The prevalence of microscopic involvement of the UGI tract can be as high as 60 % [ 12 -14 ].…”
Section: Crohn's Diseasementioning
confidence: 99%